PENDIDIKAN ISLAM TRANSDISIPLINER DAN SUMBER DAYA MANUSIA INDONESIA - Imam Mawardi (Jurnal Pendidikan Islam, 2013)
This writing describes the prossibility to have Islamic education established as transdiscipliner: that is, omitting the dichotomy between religion knowledge and general knowledge, and developing the understanding that the relatedness between the two. The method used in this study is a discourse analysis. A number of references is discussed and analysed based on the direction and purpose of the transdiscipliner concept. In fact, in the context of Islamic education, transdiscipliner curriculum that must be developed should be holistic—covering a number of problems that are closed to human and being able to develop as human resource. Human as mysterious being cannot be approached from one single discipline. Human should be understood from transdiscipline. The expected ability in Islamic education in transdiscipliner concept is the ability to view the world as a value system with its different function and task but they are still related. This connection and interconnection system should be placed in the frame of faith and good deeds.